Attachment anxiety: parenting culture, adolescence and the family film in the US. Issue 2 (3rd April 2017) - Antunes, Filipa
Abstract: Many authors have noted a connection between notions of childhood and understandings of parenting; however, debates have focused only on adults and their behaviour. This article interrogates the child's position in contemporary parenting culture using the Hollywood family film to explore how the cultural constructions of childhood and parenting may influence one another. The article analyses the reception of the family film of the 1990s and its representations of families and children to note a cultural response to the previous decade's "discovery" of the pre-teen demographic. This response highlighted the incompatibility of young adolescence and attachment parenting, constructing a new childhood ideal which returned the child to assumptions of vulnerability.